2015
DOI: 10.4236/health.2015.71016
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Dietary Restriction for Promotion of Neurohealth Benefits

Abstract: Physical exercise, whether aerobic, endurance or resistance types, plays a central role in establishing and maintaining the integrity of the brain and central nervous system (CNS). When exercise is adhered to in conjunction with selective food/drink intake and dietary restriction, it promotes neurohealth. In this article, we review the interactions of age and gender, as well as insulin and diabetes, with exercise, individuals' cognitive-affective status and its interactions with exercise propensity, all of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 157 publications
0
7
0
Order By: Relevance
“…Although increased levels of physical exercise are associated with better health and well-being [35][36][37][38], and better prognosis in psychiatric conditions, the observation of greater exercise frequency in the present study may not necessarily be an entirely positive manifestation. On the one hand, it has been observed that female patients with AN engaged in caloric restriction and excessive exercising prior to clinical treatment had larger hippocampal volumes than healthy comparison women.…”
Section: Discussionmentioning
confidence: 48%
“…Although increased levels of physical exercise are associated with better health and well-being [35][36][37][38], and better prognosis in psychiatric conditions, the observation of greater exercise frequency in the present study may not necessarily be an entirely positive manifestation. On the one hand, it has been observed that female patients with AN engaged in caloric restriction and excessive exercising prior to clinical treatment had larger hippocampal volumes than healthy comparison women.…”
Section: Discussionmentioning
confidence: 48%
“…The enduringly, but disturbingly, high level of variation depicting the physical exercise/activity profiles of AN patients that is attributed to the, either low or very high, patterns of these behaviors presents a highly relevant issue in AN [22]. It has been shown that there are differences expressed between those parents with and those without core eatingdisorder psychopathology; those parents presenting eating-disorder psychopathology reported greater perceived feeding responsibility, stronger concerns about their children's weight management and spent more time monitoring the children's intake behavior than those parents not presenting eating-disorder characteristics [23]. The notion concerning the conceptualization and measurement of pathological exercise in association with eating disorder, not least AN, is not novel, not least in its connotations with perfectionism and compulsive behaviour [24].…”
Section: Editorialmentioning
confidence: 99%
“…The purpose of this treatise is to examine the notion of physical exercise as intervention to facilitate a positive developmental trajectory, as has been observed both under normal conditions and those associated with developmental disturbance, e.g. ADHD [9][10][11][12][13][14]. Motor skills difficulties, such as balance, posture and gait and movement speed, are present in children diagnosed with ASD [15,16].…”
Section: Introductionmentioning
confidence: 99%